Do Managers Use Meeting Analyst Forecasts to Signal Private Information? Evidence from Patent Citations - Gunny, Katherine (Institutional Knowledge at Singapore Management University, 2014)
This study examines whether firms manage earnings to meet analyst forecasts to signal superior future performance. Prior research finds that firms use earnings management to just meet analyst forecasts and that these firms have a positive association with future performance (Bartov et al., 2002). There are two potential explanations for the positive association – signaling and attaining benefits that allow for better future performance (i.e., the real benefits explanation). Prior studies cannot provide evidence of signaling because they do not control for the real benefits explanation. Our research design enables us to control for the real benefits explanation because we can identify potential signaling firms within the sample of firms that just meet analyst forecasts. We use a unique database from the National Bureau of Economic Research to construct a proxy for the manager's belief about future firm value due to patents. We find that firms with more patent citations are more likely to just meet the analyst forecast and manage earnings to achieve this goal. We also find firms that just meet analyst forecasts with more patent citations have significantly better performance than firms with fewer patent citations, which is consistent with signaling and not the real benefits explanation.